Absorção de macronutrientes pela cultura do gergelim - Corrêa, Maria José Pinheiro (1994)
The present research had as its main purpose the study of the sesame (Sesamum indicum, L.) c.v. Joni, as it 'relates to the production of dry material; absorption of the macro-nutrients (N, P, K, Ca, Mg and S) at different phases of development as well as nutrients exporting through harvesting. The work, was carried out at the experimental area of the Seed analysis Laboratory of the Agrarian Sciences Center of the Ceará Federal University (UFC), from October 1993 to February 1994. The delineation employed in the research was of case-blocks with four repetitions, one cultivar and seven sampling periods. The first sample was collected 26 days after the emergence of the plantlets, and other sample collecting at regular 12 days intervals. From the collecded material (leaf, stalk, fruit) it was determined the amount of dry material as well as the macro-nutrients chemical content. It has been concluted that: the maximum accumulation of dry material in the leaves and stalks ocurred in the 78 and 87 days after emergence respectively; the accumulation of dry material on the fruits was linear and increasing, together with the crop cycle; the macro-nutrients content was found to be higher in the leaves than in the stalks, exception made to potassium; the maximum nutrients extraction ocurred, between 74 and 86 days after the plants emergence. Having its basis on the rate of nutrients absorption and the crop's curve of growth, it is reccomended to undertake fertilizing procedures divided in tree times and according to the following doses: 320 kg N/ha, 110 kg P2O5/ha and 280 kg K2O; the first fertilizing period shall be applied at sowing time (1/3 N, all the P2O5 and 1/3 K2O), the second fertilizing 25 to 30 days after plant emergence (1/3N and 1/3 K2O) and the third fertilizing (1/3 N and 1/3 K2O) 55 to 60 days after plant emergence.